2022
DOI: 10.3389/fgene.2022.1014031
|View full text |Cite
|
Sign up to set email alerts
|

RNA-sequencing analysis reveals the long noncoding RNA profile in the mouse myopic retina

Abstract: Aim: Myopia is a prevalent public health problem. The long noncoding RNA (lncRNA) mechanisms for dysregulated retinal signaling in the myopic eye have remained elusive. The aim of this study was to analyze the expression profiles and possible pathogenic roles of lncRNAs in mouse form-deprived myopia (FDM) retinas.Methods: A mouse FDM model was induced and retinas from the FDM right eyes and the contralateral eyes were collected for RNA sequencing. Gene Ontology (GO), Kyoto Encyclopedia of Genes and Genomes (KE… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
3
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 84 publications
0
3
0
Order By: Relevance
“…Previous studies have identified possible differentially expressed genes and pathways involved in myopia models [8][9][10][11]. However, there is not much of a consensus among the existing studies due to variations in animal models and experimental designs.…”
Section: Introductionmentioning
confidence: 99%
“…Previous studies have identified possible differentially expressed genes and pathways involved in myopia models [8][9][10][11]. However, there is not much of a consensus among the existing studies due to variations in animal models and experimental designs.…”
Section: Introductionmentioning
confidence: 99%
“…Recent studies have shown that lncRNAs play a crucial role in the pathogenesis of myopia [ 15 , 37 ]. It has been found that lncRNA Gm35369 might be related to myopia, and this lncRNA is mainly located in ganglion cells and horizontal cells [ 14 ]. Studies have reported that RGC alterations are associated with the occurrence and development of myopia, including changes in the number of RGCs, abnormal axonal projections and changes in protein expression in RGCs [ 19 22 , 38 ].…”
Section: Discussionmentioning
confidence: 99%
“…For example, the abnormal expression profiles of lncRNAs in the retinas of form-deprived myopia (FDM) mouse models were analyzed in a prior study. It was found that lncRNA Gm35369 might be related to myopia and that this lncRNA was mainly located in ganglion cells and horizontal cells [ 14 ]. Assessment of the differential expression of lncRNAs in the ocular posterior poles of two guinea pig myopia models (FDM and lens-induced myopia (LIM)) has revealed that lncRNA-related extracellular matrix (ECM), kinase activity, metabolism, ECM receptor interactions, glycosaminoglycan degradation and multiple functional pathways are involved in the pathogenesis of myopia [ 15 ].…”
Section: Introductionmentioning
confidence: 99%
“…FASTQ files of RNA-Seq raw reads were retrieved from the Gene Expression Omnibus (GEO). 1 The dataset (PRJNA832969) contains 12 retinal samples of male C57BL/6 J mice from six FDM and six fellow controls, and each sample contains three retinas ( Li et al, 2022 ). According to the original study, FDM was induced in the male C57BL/6 J mice at three weeks of age.…”
Section: Methodsmentioning
confidence: 99%